A multicriteria decision analysis (MCDA) tool to purchase implantable medical devices in Egypt - Baher Elezbawy; Ahmad Nader Fasseeh; Bertalan Németh; Mary Gamal; Mariam Eldebeiky; Remonda Refaat; Amr Taha; Shimaa Rabiea; Marwa Abdallah; Soha Ramadan; Hasnaa Noaman; Amany Bahaa Eldin; et al. (BMC Medical Informatics and Decision Making, 2022)
Abstract Background With the availability of several similar medical devices performing the same function, choosing one for reimbursement is not easy, especially if purchased for a large number of patients. The objective of this project was to create a multicriteria decision analysis (MCDA) tool, that captures and compares all implantable medical devices’ attributes, to provide an objective method for choosing among the available options in Egypt. Method We conducted a systematic review and expert interviews, to identify the relevant criteria for inclusion in the tool. Subsequently, a workshop was conducted, that involved experts in procuring and tendering medical devices. Experts chose the criteria, ranked them, assigned weights and scoring functions for each criterion, and then created the draft tool. A pilot phase followed; then, another workshop was conducted to fine-tune the tool. We readjusted the tool based on experts’ experience with the draft tool. Results The final tool included eight criteria, arranged according to their weightage: technical characteristics (29.4%), country of origin (19.5%), use in reference countries (14.9%), supply reliability (11.7%), previous use in tenders (9.0%), instant replacement within product variety (6.9%), pharmacovigilance (4.6%), and refund or replacement (4.0%). Each medical device was assessed on these eight criteria to achieve a final score, that was compared to the alternative devices’ scores. Price is not included in the MCDA tool, but it will be added in the financial evaluation phase. Conclusion Decisionmakers could use the MCDA tool, to make evidence-based and objective decisions for purchasing implantable devices, in the Egyptian public sector. Post price evaluation, the product with the best value will be chosen for reimbursement. Highlights We created an MCDA tool to help decision makers choose between alternative implantable medical devices in Egypt. The MCDA tool includes eight criteria, where price is evaluated as a separate step. “Technical characteristics” and “country of origin” criteria carried the highest weights, thus representing approximately 50% of the decision.